Update on the management of colchicine resistant Familial Mediterranean Fever (FMF) - El Hasbani, Georges (Orphanet J Rare Dis, 2019)
BACKGROUND: Familial Mediterranean Fever (FMF), an autoinflammatory disease, is characterized by self-limited inflammatory attacks of fever and polyserositis along with high acute phase response. Although colchicine remains the mainstay in treatment, intolerance and resistance in a certain portion of patients have been posing a problem for physicians. MAIN BODY: Like many autoimmune and autoinflammatory diseases, many colchicine-resistant or intolerant FMF cases have been successfully treated with biologics. In addition, many studies have tested the efficacy of biologics in treating FMF manifestations. CONCLUSION: Since carriers of FMF show significantly elevated levels of serum TNF alpha, IL-1, and IL-6, FMF patients who failed colchicine were successfully treated with anti IL-1, anti IL-6, or TNF inhibitors drugs. It is best to use colchicine in combination with biologics.